Magnetic properties of CoFe/FeZr/CoFe multilayers - Jun, KI; Lee, JH; Shin, KH; Rhie, K; Lee, BC (WILEY-V C H VERLAG GMBH, 2004)
Magnetic multilayers with the CoFe/FeZr (t nm)/CoFe structure were investigated, where the FeZr layer was a paramagnetic amorphous metallic alloy. Separate magnetization reversal was observed for two CoFe layers when t greater than or equal to 2.0 nm, while they were not magnetically separable for t < 2 nm. For all FeZr thicknesses, neither the GMR effect, nor interlayer exchange coupling through the paramagnetic FeZr was observed, but a negative AMR of 0.25% was observed. The wave vector mismatch at the interface is suggested for the main reason. (C) 2004 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: GIANT MAGNETORESISTANCE; SUPERLATTICES